2008
DOI: 10.1143/ptps.175.144
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation in a Sheared Ising Model: Effects of External Field

Abstract: Simulations using the Forward Flux Sampling method have shown a nonmonotonic dependence of the homogeneous nucleation rate on the shear rate for a sheared two dimensional Ising model [R. J. Allen et al, arXiv:cond-mat/0805.3029]. For quasi-equilibrium systems (i.e. in the absence of shear), Classical Nucleation Theory (CNT) predicts the dependence of the critical cluster size and the nucleation rate on the external magnetic field. We investigate the behaviour of the sheared Ising model as a function of the ext… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…Here, P A (λ) is called the splitting probability, and is the likelihood that a configuration with order parameter value λ falls back to A. In general, P A (λ) can be estimated from: (38) with f (λ) the attachment rate. In general, Eq.…”
Section: Probability Splitting Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Here, P A (λ) is called the splitting probability, and is the likelihood that a configuration with order parameter value λ falls back to A. In general, P A (λ) can be estimated from: (38) with f (λ) the attachment rate. In general, Eq.…”
Section: Probability Splitting Methodsmentioning
confidence: 99%
“…In a lattice gas, each vertex will be either occupied (n i = 1) or vacant (n i = 0). In recent years, FFS has been extensively utilized for studying the sensitivity of the nucleation kinetics in the Ising and lattice gas models to the existence and energetic properties of impurities, 34,36,41 mechanical deformations, 37,38 internal and external interfaces, 35,36,[41][42][43] and the topological properties of the underlying network. 39,40,44,45 Since nucleation will only occur if the underlying transition is first-order, all these simulations were conducted in the presence of an external magnetic field or chemical potential, and the starting basin A is always set to the respective metastable phase in each system.…”
Section: Nucleation In On-lattice Spin Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cirillo et al ͓24͔ performed a much more extensive numerical analysis of this sheared Ising model using the same dynamics. The sheared Ising model was also used by Allen et al ͓14,25͔ to study nucleation and growth processes using Forward Flux Sampling ͓26-28͔. In the latter work it was found that shear introduces competing processes ͑shear-mediated breakup at large shear rates, and shear-induced coalescence at small shear rates͒ that produce a nonmonotonic dependence of the cluster growth rate on the rate of shear.…”
Section: Introductionmentioning
confidence: 99%